It : a novel - King, Stephen, 1947- (Scribner, 2016)
It began--and ended--in 1958 when seven desperate children searched in the drains beneath Derry for an evil creature, but in 1985, Mike Hanlon, once one of those children, makes six phone calls and disinters an unremembered promise that sets off the ultimate terror.